2013
DOI: 10.1186/1471-2334-13-366
|View full text |Cite
|
Sign up to set email alerts
|

Multi-drug resistant toxigenic Vibrio cholerae O1 is persistent in water sources in New Bell-Douala, Cameroon

Abstract: BackgroundCholera has been endemic in Douala, since 1971 when it was first recorded in Cameroon. Outbreaks have often started in slum areas of the city including New Bell. Despite the devastating nature of outbreaks, always resulting in high mortality and morbidity, a paucity of information exists on the reservoirs of the causative agent, V. cholerae, and factors maintaining its persistence. This has complicated disease prevention, resulting in frequent outbreaks of cholera. We investigated water sources in Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 46 publications
(60 reference statements)
4
18
0
1
Order By: Relevance
“…However, high activities of ofloxacin and ciprofloxacin observed in our study are similar to other studies [15, 38, 39] and corroborate the use of fluoroquinolones as new alternatives for cholera treatment in some cholera endemic regions [40]. Our data and reports from other cholera endemic localities in Douala [20] therefore suggest ciprofloxacin and ofloxacin could be very good alternatives for chemotherapy during cholera or cholera-like disease outbreaks in Douala.…”
Section: Discussionsupporting
confidence: 92%
“…However, high activities of ofloxacin and ciprofloxacin observed in our study are similar to other studies [15, 38, 39] and corroborate the use of fluoroquinolones as new alternatives for cholera treatment in some cholera endemic regions [40]. Our data and reports from other cholera endemic localities in Douala [20] therefore suggest ciprofloxacin and ofloxacin could be very good alternatives for chemotherapy during cholera or cholera-like disease outbreaks in Douala.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study furazolidone was showing constant resistance between 90% to 100% also. Results similar to this study were also reported from various region of Kenya (17) and Cameroon (18). Since cholera is a non-invasive disease, drug such as co-trimoxazole which is not absorbed from gastrointestinal tract was widely used for treatment.…”
Section: Accepted Manuscriptsupporting
confidence: 80%
“…Several other workers also reported 100% resistance to co-trimoxazole from North Karnataka (19) and Cameroon (18). (12,(16)(17)(18). During the study the El Tor variants of V.cholerae were reported from 2007 onwards causing cholera outbreaks and epidemics in different parts of the state and also spread to different areas of Odisha (7,30).…”
Section: Accepted Manuscriptmentioning
confidence: 94%
See 1 more Smart Citation
“…Entretanto, a resistência apresentada por V. cholerae é um problema que tem aumentado, principalmente em países em desenvolvimento. Enquanto há relatos de resistência a um único antibiótico em vários países endêmicos da cólera (EIBACH et al, 2016;VILA et al, 2010), também há casos de cólera originados por isolados com resistência a vários antibióticos (cloranfenicol, eritromicina, kanamicina, tetraciclina e trimetropimsulfametoxazole), que foram relatados no Iran, Paquistão, Bangladesh, Índia, Nepal, Nigéria, Moçambique, Camarões e Malásia (AKOACHERE et al, 2013;AWASTHI et al, 2015;GUPTA et al, 2016;MANDAL et al, 2011;MANDOMANDO et al, 2007;MARIN et al, 2013;MATERU et al, 1997;ODEYEMI et al, 2016;OLUMIDE et al, 2017;SEDAGHAT et al, 2012;SHRESTHA., 2015).…”
Section: Patogenicidade Genes Associados à Virulência De Vibrio Cholunclassified